Meta-Analysis: The Effect of The Think Talk Write Learning Model on Students' Mathematics Learning Outcomes - Yunia Jumita Ningrum; Dadan Dasari; Abdul Wahab A (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Students' low mathematics learning outcomes remain a major issue in education, highlighting the need for more effective and innovative instructional strategies. This study aims to explain the effect of Think Talk Write learning model on learning outcomes through the use of meta-analysis. This study presents a comprehensive meta-analysis to address the limitations of previous studies, which were largely contextual and lacked a thorough quantitative overview of the effectiveness of the Think Talk Write model on students' mathematics learning outcomes. This article quantitatively analyzes the effect of the Think Talk Write model, provides a description of the data on sample size, mean, and standard deviation, and is published in a Google Scholar indexed journal. In this analysis, mean difference, Forrest plot, and publication bias were calculated using JASP software and Excel manual calculation. The results of the analysis showed that the value of I2 = 94.441 with a confidence of 0.95%. The forest plot showed a mean effect of 1.39, and the study effect size values ranged between 0.76 and 2.01. This shows that there is a significant difference between learning with the Think Talk Write model and conventional learning. In the group learning process, students who used the Think Talk Write model had better learning outcomes than students who did not use it. The analysis shows that Think Talk Write model is very important to support learning.